ANATOMI SEBELAS JENIS KAYU KURANG DIKENAL DARI SUKU MIMOSACEAE, MYRISTICACEAE DAN MORACEAE - Y l Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Gross and anatomical features of eleven lesser known wood species of Mimosaceae. Myristicaceae and Momceae were observed and described for identification pueposes. Fiber dimension were also measured and evaluated for their suitability for pulp manufacturing purposes.Members of Mimosaceae (Adenanthera pavonina and Albizia chinensis) are characterized by homoselular ray, paratracheal pa-renchyma and vestured pit. Further differenttiation is posibie based on other characters.Members of Myristicaceae (Myristica maxima and Horsfieldia sylvestris) are characterized by apotracheal banded parenchyma. vessels mostly in radial multiples and the presence of taniniferous tube in ray tissue.Further differentiation is not possible.No spesific features Were found for Moraups but two groups were recognized : 1) those brown in colour with paratrachealparenchyma and white deposit in some of their vessels (5 species) : 2) those white in colaur, aportracheal banded, parenchyma,withoute white deposit in vessel (2 species). Futher differentiation of each group is possible up to genera level.Ten out of eleven species examined contain fibers with medium quality. The rest one species, (Prainea limpato - Moraceae) contain fibers with poor quality.